Inovasi Organisasi di Era Digital: Peran Transformasi Teknologi, Kepemimpinan Adaptif, dan Budaya Berbasis Nilai Islam - Ulfa Malikatuz Zahroh; Dwi Dimiati Hartini; Mirza Gunawan Wibisono; Hilal Al Amin (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
In order to meet the difficulties of digital transformation and contemporary market dynamics, organizational innovation is essential. The main concerns of organizational innovation are discussed in this article, along with obstacles such a lack of digital skills, high implementation costs, change aversion, and inflexible company culture. A literature review using a qualitative methodology is the research strategy employed to examine sources pertaining to innovation, drivers, and inhibitors. The findings demonstrate that technological integration, flexible leadership, a positive company culture, and efficient human resource management (HRM) procedures are all necessary for innovation to succeed. Islamic principles like accountability (amanah), consistency (istiqamah), and honesty (shiddiq) also support the innovation culture. According to the article's conclusion, responsive HRM, adaptive culture, and controlled innovation can all help organizations become more resilient and competitive in the digital age.